2019
DOI: 10.3390/min9020099
|View full text |Cite
|
Sign up to set email alerts
|

Ore Genesis at the Jinchang Gold–Copper Deposit in Heilongjiang Province, Northeastern China: Evidence from Geology, Fluid Inclusions, and H–O–S Isotopes

Abstract: The Jinchang gold–copper deposit is located in Eastern Heilongjiang Province,Northeastern China. The orebody comprises primarily hydrothermal breccias, quartz veins, anddisseminated ores within granite, diorite, and granodiorite. Three paragenetic stages are identified:early quartz–pyrite–arsenopyrite (Stage 1), quartz–pyrite–chalcopyrite (Stage 2), and latequartz–pyrite–galena–sphalerite (Stage 3). Gold was deposited during all three stages and Stage 1was the major gold-producing stage. Copper is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The partitioning of fluid into vapor-rich high-salinity fluids was caused by the boiling of parental magmatic fluids ( Figure 10). 3Most of the S-type FIs were homogenized by the simultaneous disappearance of the vapor phase and daughter minerals [39]. The homogenization temperatures of the boiling inclusions were close to the quartz crystallization temperatures, which were similar to the ore formation temperatures of the Jinxiantou and Changgou deposits.…”
Section: Fluid Compositions and Pressure-temperature (P-t) Conditionsmentioning
confidence: 74%
See 1 more Smart Citation
“…The partitioning of fluid into vapor-rich high-salinity fluids was caused by the boiling of parental magmatic fluids ( Figure 10). 3Most of the S-type FIs were homogenized by the simultaneous disappearance of the vapor phase and daughter minerals [39]. The homogenization temperatures of the boiling inclusions were close to the quartz crystallization temperatures, which were similar to the ore formation temperatures of the Jinxiantou and Changgou deposits.…”
Section: Fluid Compositions and Pressure-temperature (P-t) Conditionsmentioning
confidence: 74%
“…The partitioning of fluid into vapor-rich high-salinity fluids was caused by the boiling of parental magmatic fluids ( Figure 10). (3) Most of the S-type FIs were homogenized by the simultaneous disappearance of the vapor phase and daughter minerals [39].…”
Section: Fluid Compositions and Pressure-temperature (P-t) Conditionsmentioning
confidence: 99%
“…A magmatic source in hydrothermal deposits implies that the δ 34 S values are near (0 ± 3‰) [98,99]. Previous studies have revealed that the sulfur isotopic composition of sulfide minerals depend on the δ 34 S of source materials, and also on the physicochemical condition (pH value, temperature, ion activity, and oxygen fugacity), as well as the evolution of the hydrothermal fluids [100,101]. The δ 34 S variation in the magmatic-hydrothermal deposit is also caused by magma contamination via interactions with country rocks, and typically assigned to the assimilation of sulfur from the wall rocks [97].…”
Section: Source Of the Ore-forming Materialsmentioning
confidence: 99%
“…Figure 15. Sulfur isotopic compositions of the Kargah Cu-Pb polymetallic deposit as compared with the magmatic-hydrothermal deposits and other geological settings, (after [9,43,44]); data of the Erdaokan Ag-Pb-Zn deposit from Yuan et al [43]; Bianjiadayuan Ag-Pb-Zn deposit from Zhai et al [104]; Jiawula Ag-P-Zn deposit from Niu et al [85] ; Sandaowanzi deposit from Zhai et al [105]; Jinchang Gold-Copper deposit from Li et al [100]; Baoshan, Shuikoushan, and Kangjiawan Pb-Zn deposits from Zou [109]; Yongxin deposit from Yuan et al [44]. [9,43,44]); data of the Erdaokan Ag-Pb-Zn deposit from Yuan et al [43]; Bianjiadayuan Ag-Pb-Zn deposit from Zhai et al [104]; Jiawula Ag-P-Zn deposit from Niu et al [85]; Sandaowanzi deposit from Zhai et al [105]; Jinchang Gold-Copper deposit from Li et al [100]; Baoshan, Shuikoushan, and Kangjiawan Pb-Zn deposits from Zou [109]; Yongxin deposit from Yuan et al [44].…”
Section: Source Of the Ore-forming Materialsmentioning
confidence: 99%
“…The primary fluid inclusions trapped during the mineralization stages are H 2 O-NaCl, unsaturated, and homogenize either to the vapor or to the liquid with Th of 300-430 • C, their salinity is 2-16 wt % NaCl equiv. and the density is 0.43 to 0.94 g/cm 3 . Although Tocantinzinho shows similarities with magmatic-hydrothermal oxidized calc-alkaline granite-related gold deposits classified as porphyry gold deposits, it has been classified with porphyry-style gold deposits, because it lacks some features of Phanerozoic porphyry-type deposits.…”
mentioning
confidence: 99%